Adaptive Door Opening Control Algorithm of Bio-Inspired Mobile Manipulator Based on Synchronous Sensing - Wu, Wenping; Liu, Wansu (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract: At present, the research of robot door opening method is basically realized by identifying the door handle through the synchronous sensing system on the premise that the bio-inspired mobile manipulator is located in front of the door. An adaptive door opening strategy of bio-inspired mobile manipulator based on synchronous sensing system is proposed. Firstly, the random delay distribution in clock synchronization technology is analyzed in detail, and its distribution is verified on the experimental platform of adjacent nodes. Based on the Gaussian distribution of random delay, the relative frequency offset and relative phase offset of adjacent nodes are calculated. The clock synchronization of network cable sensor nodes is realized; Secondly, based on the information data of synchronous sensing system, this paper realizes target detection and tracking based on depth network; In addition, based on the sliding mode control theory, the dynamic model of nonholonomic bio-inspired mobile manipulator is applied. Finally, a robust adaptive sliding mode control method for nonlinear systems with input gain uncertainty and unmatched uncertainty is proposed by combining adaptive backstepping with sliding mode control. By adding sliding mode control in the last step of adaptive backstepping, the uncertainty of the system is compensated and the system trajectory is maintained on the specified sliding mode manifold. The tracking control and stability control of nonholonomic bio-inspired mobile manipulator are simulated. The experimental and simulation results show that the control method proposed in this paper is effective and feasible. Keywords: Prediction model; bio-inspired mobile manipulator; synchronous sensing; adaptive door opening control; sliding mode control